Geographic Regions for Crop Cost-Return Budgets - Langemeier, Larry N. (My University, 1996)
This publication outlines the regional areas of Kansas for the crop cost-return guides.
MF2235_1996_10
Keywords: MF2235; Economics; Crops; MF